KEPEMIMPINAN KEPALA SEKOLAH PADA SATUAN PENDIDIKAN ISLAM DALAM UPAYA MENINGKATKAN PROFESIONALISME GURU - Radia Hijrawan (STKIP Pesisir Selatan, 2019)
The leader in the organization is very important because the leader determines whether or not the wheels of government are running. Given the importance of leaders, it can be seen that the main function of leadership in education units, such as the headmaster is to create teaching and learning situations so that teachers can teach and students can learn well. This research is descriptive analytic which examines the theories of experts on all matters relating to the leadership of principals in Islamic education units, then analyzes it to find the efforts of teacher professionalism in teaching. What will be discussed in this paper is how the leadership of the principal, the task of the principal, develops the professionalism of the teacher and the leadership of the principal in an effort to improve teacher proceduralism, so that the purpose of this research is to develop teachers as reliable teachers, and can shape character and morality children of the nation